2014
DOI: 10.1371/journal.pone.0105750
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Donor-Deficient Diet during Development Can Affect Fear and Anxiety in Adulthood in C57BL/6J Mice

Abstract: DNA methylation is one of the essential factors in the control of gene expression. Folic acid, methionine and choline (methyl donors)–all nutrients related to one-carbon metabolism–are known as important mediators of DNA methylation. A previous study has shown that long-term administration of a diet lacking in methyl donors caused global DNA hypermethylation in the brain (Pogribny et al., 2008). However, no study has investigated the effects of a diet lacking in methyl donors during the developmental period on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 56 publications
1
32
2
Order By: Relevance
“…Each cage housed 2 rats. Diet restriction was done to ensure equal feeding between groups since previous studies had reported diminished food intake in rodents receiving a methyl-depleted diet [61, 62]. Animals were weighed each week starting on the first day of diet exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Each cage housed 2 rats. Diet restriction was done to ensure equal feeding between groups since previous studies had reported diminished food intake in rodents receiving a methyl-depleted diet [61, 62]. Animals were weighed each week starting on the first day of diet exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Bidirectional changes in the methylation status of several memory-related genes, including Pp1cb, reelin, and Bdnf, have also been found in the hippocampus following fear learning (Miller and Sweatt 2007;Lubin et al 2008). Consistent with these findings, mice fed a diet deficient in the methyl donors folate, methionine, and choline from 3 to 6 wk of age to drive a global reduction in DNA methylation levels, have impaired fear memory formation that persists into adulthood (Ishii et al 2014). Finally, cortical DNA methylation supports the storage of remote (30-d-old) fear memory (Miller et al 2010), suggesting that targeting this epigenetic mechanism may be useful in treating the pathological persistence of fear memories in PTSD.…”
Section: The Neuroepigenetics Of Fear Memorymentioning
confidence: 54%
“…We observed in literature significant effects of HFD on rats cognition [32], and the adverse effects of methyl donor-deficient diet during brain development on memory and anxiety in adulthood in mice [33]. In addition, previous studies demonstrated significant relationship between maternal fructose diet and metabolic disorders in their offspring [34].…”
Section: Discussionmentioning
confidence: 99%
“…Methyl donors is a factor of regulation of epigenetic mechanisms well-known as DNA methylation and histone acetylation involved actively in control of gene expres- [56]. Otherwise, a previous paper reported that methyl donors' supplementation diet induces an increasing of NMDA receptor subunit, NR2B gene expression in hippocampal cells [33].…”
Section: Discussionmentioning
confidence: 99%